Analisis Proses Produksi UMKM Toko Batik Bahalap di Kota Palangka Raya - I Putu Jonathan; Jonathan Giovanni; Achmad Syamsuddin (IAI Nasional Laa Roiba Bogor, 2025)
Explaining the distinctiveness and examining the manufacturing method of Bahalap batik, the exceptional product of Palangka Raya MSMEs, is the aim of this study. This study employs a qualitative approach to literature review. A variety of information gathering techniques are used in this study, including direct observation, interviews, archival materials, and pertinent scientific publications or journals. The sample for this study was chosen using purposive sampling, which is based on the following criteria: the company must be in the SME (Small – Medium Enterprise) category, be a shop owner and producer of Bahalap Batik, have a production process that combines conventional and semi-modern methods, have been producing and marketing batik handicrafts for at least five years, operate continuously, and be making efforts to expand. Although the Bahalap batik production process has generally followed business protocols, it still requires improvement in terms of efficacy and efficiency, which can be accomplished by updating its more current production equipment and hiring more skilled human resources..